The Transparency Paradox: How Digital Accountability Can Inflate Public Costs in Low-Trust Environments - Ugural, Mehmet Nurettin; Aghili, Seyedarash (ASCE-AMER SOC CIVIL ENGINEERS, 2026)
Digital governance reforms are widely promoted to enhance public sector efficiency, yet their economic impacts in varied institutional contexts remain underexamined. This study investigates a critical paradox where a mandatory e-procurement reform in Turkey, intended to reduce costs, instead triggered significant cost escalation amidst severe macroeconomic volatility. Employing a fortified difference-in-differences interrupted time series (DiD-ITS) model, we disentangle the policy's impact from the confounding effects of a concurrent currency crisis by comparing Turkey's cost trajectory (2014-2023) with that of a composite control group of five regional peers with European Union (EU)-harmonized procurement frameworks. This causal analysis is supplemented by computational text modeling to identify the underlying institutional mechanism. Our findings reveal that, after controlling for exchange rate effects, the reform caused a statistically significant 2.15 percentage-point quarterly acceleration in construction costs. We trace this material failure to a friction premium-representing the costs of administrative burdens and regulatory risks-which firms rationally priced into tenders in response to a sharp institutional shift toward formal compliance. The primary contribution of this study is the identification and empirical validation of the friction premium multiplier, a generalizable mechanism explaining how mimetic digital reforms can paradoxically fail in low-trust, high-volatility contexts. By providing robust, causally identified evidence of these mechanisms, this research clarifies how and why such reforms can lead to unintended negative consequences.
Keywords: Causal inference; Difference-in-differences; Digital governance; E-procurement; Administrative burdens; Institutional trust; Policy paradox; Macroeconomic volatility; MANAGEMENT; ECONOMICS; PROMISES; POLICY; Engineering